The Psychological Perspectives of Violence: Consequences, Dimensions, and Effects | الروئ السيكولوجية للعنف: المآلات والأبعاد والآثار - Abaker Abdelbanat (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
The study addressed the hidden psychological violence as a form of human violence, and the most effective in the individual life and the group, and different forms of violence from one society to other physical factors of the different cultural and intellectual heritage, in addition to the physiological and ideological influences. Against this psychological and physical variables different violence patterns miss when religious faith and legal restraint, and here it requires that there be punishment for the perpetrators of such crimes and often community creates strategies to confront violence in all its forms and in different ways. Researcher used descriptive and analytical method to the study of types, causes and history of violence phenomenon must be disposed of consequences.